The Old Testament and modern study a generation of discovery and research - Rowley, Harold Henry, 1890-1969; Society for Old Testament Study (Oxford, UK Clarendon, 1951)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. -- commentaries